2020
DOI: 10.1002/slct.202002086
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Adsorption Case for Efficient Capture of VOCs Using Biomass‐based Corncobs via a Carbonized Strategy

Abstract: Herein, we report excellent corncobs‐derived carbon adsorbent by the special KOH chemical activation method which specific to selective adsorption removal of volatile organic chemicals (VOCs) under humid conditions. The obtained corncobs‐derived carbon adsorbent affords the enhanced adsorption removal capacities for volatile benzene (851.3 mg g‐1) and toluene (854.9 mg g‐1), outperforming comparative that derived from KOH grind means, which are 3 times higher than those of commercial activated‐carbon (benzene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 41 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Metal–organic framework (MOF)-derived materials such as the graphene–MOF hybrid demonstrated enhanced sensing performance for the detection of volatile organic compounds (VOC) biomarkers. The material was reportedly capable of sensing the VOC biomarkers at a minuscule level between 2.82 and 22.6 ppm . The high detection level and selectivity of the MOF-derived sensor toward the biomarkers were apparently due to the microporous nature of the MOF, which was reportedly capable of capturing adsorbates through esoteric π–π interaction, π-complexation, and H-bonding. Despite the many benefits that the MOF has to offer, this material typically exists in an extremely fine powdery form in nanosize scale that becomes difficult to recover or retain in the system, resulting in lower process efficiency and sustainability when it is applied as a gas adsorbent. …”
Section: Introductionmentioning
confidence: 99%
“…Metal–organic framework (MOF)-derived materials such as the graphene–MOF hybrid demonstrated enhanced sensing performance for the detection of volatile organic compounds (VOC) biomarkers. The material was reportedly capable of sensing the VOC biomarkers at a minuscule level between 2.82 and 22.6 ppm . The high detection level and selectivity of the MOF-derived sensor toward the biomarkers were apparently due to the microporous nature of the MOF, which was reportedly capable of capturing adsorbates through esoteric π–π interaction, π-complexation, and H-bonding. Despite the many benefits that the MOF has to offer, this material typically exists in an extremely fine powdery form in nanosize scale that becomes difficult to recover or retain in the system, resulting in lower process efficiency and sustainability when it is applied as a gas adsorbent. …”
Section: Introductionmentioning
confidence: 99%
“…The improved surface function enables greater chemical interactions, surface modification is a crucial role in enhancing VOC fixation. Shen et al ( 2020 ) reported that the activation of corncobs-derived carbon adsorbent with KOH improves the selectivity of VOC adsorption (851.3 and 854.9 mg/g for benzene and toluene, respectively) three times better than the adsorption capacities using a commercial activated carbon. Li et al ( 2011 ) studied the chemical modification of coconut shell–based activated carbon towards the fixation of hydrophobic VOC (o-xylene).…”
Section: Adsorption Of Pollutants In Air Phasementioning
confidence: 99%
“…In recent years, due to its advantages of reasonable utilization of resources and easy preparation, waste biomass‐derived activated carbon prepared have been gradually applied to various environmental control fields such as the electric chemical water treatment of food organic pesticide removal, gas or heavy metal ions adsorption capture [1–4] . Notably, the adsorption capture of VOCs using biomass‐derived AC has become popular because of serious requirement of environmental control, but the resultant great adsorption capacity and selectivity of VOCs ceaselessly demand improved structural properties and surface character of AC obtained through rational synthesis control, [5–10] which has not been explored yet.…”
Section: Introductionmentioning
confidence: 99%